2020
DOI: 10.1016/j.ijppaw.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Review on parasites of wild and captive giant pandas (Ailuropoda melanoleuca): Diversity, disease and conservation impact

Abstract: The giant panda ( Ailuropoda melanoleuca ) is a rare species with a small global population size, and lives in the wild in only a few fragmented mountain ranges of Southwest China. Parasitic infections are among the important causes of death of giant pandas that hamper their group development. We reviewed the parasitic infections prevailing in giant pandas, and the parasitic diversity, diseases and their impact on conservation of this animal. A total of 35 parasitic species were document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…Although breeding enclosures are designed to provide proper physical conditions, captive animals inevitably experience chronic stress, which can lead to immunosuppression and disease [ 9 ]. Parasites can rapidly spread from one individual to multiple individuals under high-density captive conditions [ 41 , 42 ]. Additionally, compared to the captive crocodile lizards, the sample size was smaller in the wild crocodile lizards, and thus may be more likely to contain non-infected or slightly infected individuals, while missing the rarer heavily infected individuals [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although breeding enclosures are designed to provide proper physical conditions, captive animals inevitably experience chronic stress, which can lead to immunosuppression and disease [ 9 ]. Parasites can rapidly spread from one individual to multiple individuals under high-density captive conditions [ 41 , 42 ]. Additionally, compared to the captive crocodile lizards, the sample size was smaller in the wild crocodile lizards, and thus may be more likely to contain non-infected or slightly infected individuals, while missing the rarer heavily infected individuals [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tick infestation occurs in companion animals, livestock, and humans, as well as in wildlife such as the flagship species, giant pandas ( 3 8 ). Indeed, the blood-sucking ticks are common ectoparasites infesting wild and captive giant panda populations ( 9 , 10 ). Their infestations can cause dermatitis, anemia, inflammation, exhaustion, and even death in giant pandas ( 7 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the blood-sucking ticks are common ectoparasites infesting wild and captive giant panda populations ( 9 , 10 ). Their infestations can cause dermatitis, anemia, inflammation, exhaustion, and even death in giant pandas ( 7 , 9 ). The hard tick infestation in giant pandas was first recorded in 1985 ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal tract of giant pandas is readily damaged by undigested bamboo fibers and parasitic infection. Even more regrettably, a large number of opportunistic pathogens from Enterobacteriaceae often cause secondary infections and lead to intestinal inflammation ( 3 , 4 ). While antibiotics are widely used to treat intestinal infections in the giant panda, recent studies have demonstrated widespread antibiotic resistance among fecal isolates of Escherichia coli ( E. coli ), a prominent member of the Enterobacteriacae family.…”
Section: Introductionmentioning
confidence: 99%